Intensifying Gated Exclusiveness of Apartment Complex Boundary Design in Seoul, Korea - Kim, Hyo-Jin; Hwang, Soe Won (International Planning History Society Proceedings, 2018)
The proliferation of private residential development is evident worldwide. In Seoul, these developments have distinctive spatial and morphological characteristics. Originally, government housing policies drove the construction of apartment complexes to ensure massive housing supply. Over time, development shifted, becoming more market-driven, aimed at the middle class, and built by the private sector. During the late 1990s, an increase in luxury high-rise apartment complexes increased, reflecting a tendency to live in a socioeconomically homogeneous community and propelling the proliferation of self-contained gated communities. To understand the continually increasing exclusive nature of apartment complexes in Seoul, we examine two areas with apartment complexes of different periods and development methods: Mok-dong, where the 1980s ‘Housing Site Development’ resulted in the simultaneous construction of multiple apartment complexes according to a single master-plan, and Geumho-dong, a neighbourhood transforming by apartment complexes under ‘Housing Redevelopment’ from the 1980s to the present. The research focused on 28 complexes, and measured the surrounding vertical borders, pedestrian paths, and roadways, and access control. Tracing these features over time, we investigated the increasingly exclusive nature and decreasing public nature of apartment complexes, consequences of development for physical and social space during different periods, and degree of public or private intervention.